2009
DOI: 10.1074/jbc.m109.049056
|View full text |Cite
|
Sign up to set email alerts
|

A Polarity Probe for Monitoring Light-induced Structural Changes at the Entrance of the Chromophore Pocket in a Bacterial Phytochrome

Abstract: Light-induced structural changes at the entrance of the chromophore pocket of Agp1 phytochrome were investigated by using a thiol-reactive fluorescein derivative that is covalently attached to the genuine chromophore binding site (Cys-20) and serves as a polarity probe. In the apoprotein, the absorption spectrum of bound fluorescein is red-shifted with respect to that of the free label suggesting that the probe enters the hydrophobic chromophore pocket. Assembly of this construct with the chromophores phycocya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 62 publications
1
9
0
Order By: Relevance
“…Previous studies with Agp1 indicated that mobility of ring A is required for photoconversion as follows: Agp1 assembled with synthetic chromophores in which the methine bridge between rings A and B is arrested in Za or Zs stereochemistry photoconverted either to a blueshifted adduct or to a species with unchanged absorbance maximum (52). Moreover, Agp1 with a fluorescein label at the position of the chromophore-binding site shows that the local environment of ring A changes significantly upon photoconversion (53).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies with Agp1 indicated that mobility of ring A is required for photoconversion as follows: Agp1 assembled with synthetic chromophores in which the methine bridge between rings A and B is arrested in Za or Zs stereochemistry photoconverted either to a blueshifted adduct or to a species with unchanged absorbance maximum (52). Moreover, Agp1 with a fluorescein label at the position of the chromophore-binding site shows that the local environment of ring A changes significantly upon photoconversion (53).…”
Section: Resultsmentioning
confidence: 99%
“…Three native cysteines, Cys-20, Cys-279, and Cys-295, all of them are potential binding sites for MTSL, can be found in the sequence of wild-type Agp1 phytochrome. Cys-279 and Cys-295 are deeply buried in the protein and not easily accessible for various labels (28). Nevertheless, they were successfully replaced by other amino acids without affecting the spectral properties or the enzymatic function of phytochrome.…”
Section: Native Cysteines In Agp1 Phytochromementioning
confidence: 99%
“…Depending on the sample, we have observed varying efficiency of chromophore binding with typical values of 65-80% for the mutants presented here. Consequently, unoccupied Cys-20 could be accessible for other re-agents (28). Therefore, both the introduced cysteine and also to some extent Cys-20 were available for covalent linkage of cysteine-specific MTSL in each of the samples.…”
Section: Native Cysteines In Agp1 Phytochromementioning
confidence: 99%
“…[43] This interpretation is consistent with conclusions derived from the UV/Vis spectra of Agp1 adducts with conformationally locked biliverdin (BV) chromophores, CD spectroscopy and measurements with a polarity probe. [16,41,[44][45][46][47][48] To identify further localised structural changes of the chromophore, we take into account the results of the DFT calculations. Although these calculations refer to the cofactor in vacuo and thus are associated with intrinsic uncertainties, the calculated spectra help in identifying the nature of the characteristic difference band pairs below 1270 cm À1 in the Pfr/Pr difference spectrum.…”
Section: Band Assignment and Structural Changes Associated With Pfr Fmentioning
confidence: 99%